Gender disparities in higher education: development and validation of the FACT-GÉN instrument - Beroíza-Valenzuela, Francisca; Salas-Guzmán, Natalia; Huepe, David (Frontiers in Education, 2024)
IntroductionGender stereotypes considerably influence human behavior, creating gaps between men and women in higher education. Society faces the challenge of preventing the loss of human talent in Science, Technology, Engineering, and Mathematics (STEM) disciplines and Social Sciences and Humanities (SSH). However, it remains unclear which factors influence the gender gap that may hinder attracting and retaining female talent in these fields. This study aimed to develop and validate an instrument, the ‘Assessing Gender Gap Factors in Higher Education’ (FACT-GÉN), to identify and measure the factors influencing the gender gap.MethodThis study employed an instrumental design to develop and validate the ‘Assessing Gender Gap Factors in Higher Education’ (FACT-GÉN) instrument. Using a cross-sectional quantitative approach, data were collected from 851 students across STEM and Social Sciences and Humanities (SSH) disciplines to ensure the instrument’s reliability and validity. Internal Consistency Analysis was conducted to assess the reliability of the identified factors, followed by Exploratory Factor Analysis (EFA) to identify underlying structures, and Confirmatory Factor Analysis (CFA) to validate the instrument’s structure.ResultsThe model demonstrated a good fit to the data, with indices such as CFI (0.911), TLI (0.894), and RMSEA (0.049), supporting its validity. The scaled chi-square difference test confirmed the adjusted model’s superiority over the null model [χ2_diff(4) = 30.805, p < 0.001]. Internal consistency was acceptable, with Cronbach’s alpha ranging from 0.62 to 0.78, and McDonald’s omega from 0.69 to 0.80. The strong factor loadings and significant correlations between the latent factors validated the model’s structure, making it a reliable tool for addressing the gender gap in academic fields.DiscussionThe validated instrument offers valuable data for research and policy, aiding efforts to mitigate the gender gap and promote equity in academia. This study highlights the instrument’s effectiveness in identifying barriers and formulating solutions for gender equality, thus filling a critical gap with a reliable tool to address the gender gap in higher education.